KAJIAN FISIOLOGI PERBEDAAN KADAR LENGAS TANAH DAN KONSENTRASI GIBERELIN PADA KEDELAI (Glycine max L.) - Indah Permanasari; Endang Sulistyaningsih (Jurnal Agroteknologi, 2013)
The objective of this research was to observ physiological process on soybean with diifferent soil moisture content and gibberelic acid concentration. The research was conducted at Experimental Field of KP4 Gadjah Mada University in Kalitirto, Yogyakarta. The research using split-plot design 5x3 factorial with 3 replications. The major plot was soil moisture content, which was arranged by randomized complete block design, consisted of 5 soil moisture content levels: 100, 80, 60, 40, and 20% field capacity. The Sub-plot was the concentration of gibberelic acid with 3 levels: 0, 100, and 200 ppm. The results showed that declining soil moisture content 60% soil capacity decreased transpiration rate 25,5%, leaf area and plant growth rate 2-6 WAP 11.25%. Interaction of soil moisture content 80% field capacity and 100 ppm gibberelic acid concentration increased plant dry weight 6 WAP.